2018
DOI: 10.1111/sms.13045
|View full text |Cite
|
Sign up to set email alerts
|

The impact of strength level on adaptations to combined weightlifting, plyometric, and ballistic training

Abstract: The purpose of this investigation was to determine whether the magnitude of adaptation to integrated ballistic training is influenced by initial strength level. Such information is needed to inform resistance training guidelines for both higher- and lower-level athlete populations. To this end, two groups of distinctly different strength levels (stronger: one-repetition-maximum (1RM) squat = 2.01 ± 0.15 kg·BM ; weaker: 1.20 ± 0.20 kg·BM ) completed 10 weeks of resistance training incorporating weightlifting de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 39 publications
9
73
0
1
Order By: Relevance
“…The study ascertained that the use of the combined method of strength development and the circuit training method in a one-month physical training cycle positively affected the overall development of motor abilities in the 6 th -8 th grade boys. The obtained results of the study characterize the peculiarities of the dynamics of middle schoolers' motor fitness and supplement the data of Ivashchenko et al [17], James et al [18] on the holistic character of motor abilities development in children and adolescents; the data of Blagrove et al [19], Prykhodko [20] on the regularities of motor abilities development in children and adolescents.…”
Section: Pedagogics Psychologysupporting
confidence: 78%
“…The study ascertained that the use of the combined method of strength development and the circuit training method in a one-month physical training cycle positively affected the overall development of motor abilities in the 6 th -8 th grade boys. The obtained results of the study characterize the peculiarities of the dynamics of middle schoolers' motor fitness and supplement the data of Ivashchenko et al [17], James et al [18] on the holistic character of motor abilities development in children and adolescents; the data of Blagrove et al [19], Prykhodko [20] on the regularities of motor abilities development in children and adolescents.…”
Section: Pedagogics Psychologysupporting
confidence: 78%
“…Further research indicated that while younger athletes may improve their change of direction performance using plyometric exercise, older athletes may display greater benefits [156]. It should be noted that stronger individuals may receive greater training benefits from PT compared with weaker individuals [171,172]. In summary, it is important to begin a PT progression with youth athletes with low intensity plyometric exercises with an appropriate training volume before progressing them to higher training volumes and eventually higher intensity plyometric exercises.…”
Section: Plyometric Trainingmentioning
confidence: 97%
“…In contrast, stronger individuals may benefit more from AEL and high intensity PT than their weaker counterparts. For example, previous research suggests that stronger individuals may benefit more from advanced methods of training such as PT [110,111]. This is likely due to their ability to tolerate greater ECC force and RFD ECC .…”
Section: Training Experiencementioning
confidence: 99%